Noncommunicable disease risk factors among the trainee doctors of a tertiary level diabetes hospital in Bangladesh - Tonima Sultana; Mithila Faruque; Palash Chandra Banik; Sharmin Sultana; Feroz Amin; Mohammad Mostafa Zaman (Lifestyle Medicine, 2021)
Abstract Background Doctors, despite being the public health leaders, are predisposed to the early development of chronic noncommunicable diseases (NCDs). This study was done to determine the prevalence of risk factors of NCDs among doctors. Methods A cross‐sectional study was conducted among the doctors of a course under the Distance Learning Program at BIRDEM General Hospital, Dhaka. It was done from March 2015 to February 2016. Data were collected using a self‐administered questionnaire, and physical and biochemical measurements. However, the measured variables were collected by the investigators. WHO STEPS questionnaire V 3.1, with adaptation to the local context, was used. Results A total of 404 (223 men and 181 women) of 451 registered doctors participated (89.6%) in the study. The prevalence of smoking was 18.8% among men, and there was no woman smoker. Among the respondents, 17% of men and 0.6% of women drank alcohol at least once in their lifetime. Low physical activity (<600 MET‐min/week) was reported by 44.4% of men and 34.3% of women. Less than a quarter of them (22.3%) consumed five or more servings of fruit and vegetables. Almost 13% had high blood pressure, and 44.8% were overweight or obese. A total of 3.2% were diabetic, and 5.9% had hypercholesterolemia. Conclusion High prevalence of NCD risk factors among the doctors in this study highlights the need to create awareness among them.